What is the best step technique for swimming relay starts? - Veiga, S.; Fischer, S.; Qiu, X.; Stosic, J.; Fuhrmann, S.; Kibele, A.; Braun, C. (Journal of Sports Science & Medicine, 2025)
There is a great heterogeneity in the starting techniques used by international-level swimmers in relay events. The aim of the present study was to analyse and compare the two most commonly used relay start techniques by male and female competitive swimmers. Thirteen males and seven females national and international-level swimmers performed several 25-m trials with their preferred relay start (n = 91, short-step; n = 54, long-step technique). Linear mixed models examined the effects of gender and start technique, with 5-m start times as a covariate. Swimmers performing long-step showed faster 5-m (0.09 s, d = 1.10) and 10-m (0.09 s, d = 0.39) times than those performing short-step starts, regardless of gender (all p < 0.001). This was the result of i) longer block times, ii) faster horizontal velocities with lower peak forces during the leg step and iii) faster velocities with higher peak forces when driving-off the block in the long-step technique. In both relay techniques, females showed 0.11 s (d = 1.38) longer 5-m and 0.69 s (d = 2.99) longer 10-m (both p < 0.001) times compared to males with longer block times and slower velocities in all key events. Swimmers should take advantage of the new starting platforms to apply long-step start techniques that increase horizontal displacement but also forward velocity before leaving the Blöcken.